The Mechanism of RMB Exchange Rate Policy Affecting China's Digital Trade - Wang Taijie (Journal of Frontier in Economic and Management Research, 2025)
Among the many economic policies of the government, exchange rate policy is one of the most important policies, especially in foreign trade and digital trade. This paper examines the impact of our country's exchange rate policy on its digital trade. The study finds that when the RMB depreciation policy is implemented, it has a significant positive impact on the development of digital trade in our country, and this conclusion is still valid after the robustness test. According to the analysis of the mediation effect model, e-commerce enterprises are the intermediary channel for the depreciation of RMB to promote the development of digital trade in our country. After heterogeneity analysis, it is found that the impact of RMB exchange rate policy on digital trade will have different characteristics in different regions, and the impact on the eastern region is the most obvious. Moreover, its exchange rate policy still has a certain lag effect. The study provides valuable insights for coordinating exchange rate policies and digital trade in developing countries.